2019
DOI: 10.1136/ebmental-2019-300093
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile apps and technologies in child and adolescent mental health: a systematic review

Abstract: QuestionThis review will aim to critically evaluate the currently available literature concerning the use of online mobile-based applications and interventions in the detection, management and maintenance of children and young people’s mental health and well-being.Study selection and analysisA systematic literature search of six electronic databases was conducted for relevant publications until May 2019, with keywords pertaining to mental health, well-being and problems, mobile or internet apps or intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 29 publications
0
49
0
1
Order By: Relevance
“…First, few evidence-based digital interventions developed for clinical trials are publicly accessible [ 11 ], and those that are accessible attract far fewer users than commercially popular but untested alternatives (eg, Headspace) [ 12 ]. Indeed, the most frequently downloaded mental health apps include few to no treatment elements found in empirically supported psychotherapies [ 13 , 14 ]. Second, digital intervention attrition rates differ markedly in clinical trials and “real-world” contexts.…”
Section: Introductionmentioning
confidence: 99%
“…First, few evidence-based digital interventions developed for clinical trials are publicly accessible [ 11 ], and those that are accessible attract far fewer users than commercially popular but untested alternatives (eg, Headspace) [ 12 ]. Indeed, the most frequently downloaded mental health apps include few to no treatment elements found in empirically supported psychotherapies [ 13 , 14 ]. Second, digital intervention attrition rates differ markedly in clinical trials and “real-world” contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that for many mental health apps information on the design and testing processes is not available [6]. The aim of the present paper is to describe the development and design process, while ongoing, of a new transdiagnostic mental health app for children.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that digital mental health interventions can be efficacious in both preventing and treating mental health problems in young people [4]- [6], recent systematic reviews also found that in comparison to the adult literature, research investigating the effectiveness of mobile interventions for young people is still lagging [6], [7]. Only a few apps have been designed and tested specifically for young people and especially children, thereby highlighting the evidence gap and limited availability of suitable digital interventions for this age group.…”
Section: Digital Mental Health Landscape For Youthmentioning
confidence: 99%
“…The digital health app space and scope continues to rapidly evolve, [17][18][19] with many new apps appearing as others disappear. As a group, however, the quality, features and attributes of the top apps we examined does not appear to be changing as quickly.…”
Section: Discussionmentioning
confidence: 99%